Peran Audit dan Hukum dalam Keamanan Informasi, Mengenalkan Aspek Hukum, Aturan, dan Bukti Digital yang Berlaku di Indonesia. - Anisa Sofiana; Adam Tabrani; Nabila Andriani; Ade Novia Maulana (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the importance of identity management and strong This research aims to analyze the convergence between information systems auditing and the cyber security legal framework in Indonesia. Amidst the escalation of cyber threats targeting national critical infrastructure, information security is no longer merely a technical issue but a binding legal obligation. This study highlights how the audit process functions as a compliance validation mechanism against positive regulations in Indonesia, specifically the Personal Data Protection Law (UU PDP) and the Electronic Information and Transactions Law (UU ITE). The research method used is descriptive qualitative with a juridical-normative approach. The results of this study are expected to map out procedures for handling digital evidence that are valid in the eyes of Indonesian law and formulate audit standards capable of mitigating legal risks for organizations. Initial findings suggest that the integration of standardized audit logs (ISO 27001) is crucial in digital forensic evidence in court